Real-Time PCR Detection of Respiratory Syncytial virus (RSV) among Adults with Pneumonia - Y. Fadhil, Hula (Iraqi Journal of Science, 2023)
This study aimed to confirm the presence of RSV using real-time PCR in nasaland throat swabs which had no visible cytopathic effect in tissue culture techniquefrom adults of moderate-to-severe pneumonia with influenza-like illness. Results ofreal-time RT-PCR found that viral RNA in 11.63% (5/43) of adult with pneumoniaand flu-like illness symptoms. A significant incidence of RSV infection in Dec. andJan. 2014 was appeared among patients aged more than 45 years. The resultsshowed that viral load significantly associated with disease severity. In conclusion,multiplex RT-PCR is recommended to diagnose RSV and influenza viruses inwinter season in older patients with pneumonia and can decrease sever illness in theelderly.